Transformational Leadership, Work Culture, Employee Engagement, Job Satisfaction, Turnover Intention in Banks - Suseno Hadi Purnomo; Abdul Haeba Ramli; Cherie Anne S. Banca (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The objective of this study is to analyze the influence of transformational leadership, organizational culture, employee engagement, and job satisfaction on turnover intention. This research was conducted in a private banking company located in DKI Jakarta Province. The sample consisted of 221 employees, selected using the saturated sampling method. Data collection was conducted through questionnaires, and the analytical method used was multiple linear regression. The results of this study indicate that transformational leadership, organizational culture, employee engagement, and job satisfaction have a significant positive effect on turnover intention. The theoretical implication of this study is that transformational leadership, a strong organizational culture, and high employee engagement can effectively reduce turnover intention if managed professionally and strategically. Keywords: transformational leadership, work culture, employee engagement, job satisfaction, turnover intention.